Menanamkan Konsep Pengelolaan Keuangan Bijak untuk Generasi Muda melalui Literasi Keuangan - Suni, Ulung Muamar; Subagiyo, Muhamad; Solihah, Ria Anisatus; Nugraha, Hendri Hermawan Adi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Wise financial management from an early age is an important foundation in building a young generation that has financial awareness. This community service activity aims to instill the concept of financial literacy in children aged 5-7 years so that they understand the value of money, needs, and the importance of saving. The method used is an educational approach through interactive activities such as games, simple transaction simulations, and casual discussions. The activity was carried out on May 22, 2024 in Dukuh Kayunan Barat, Kayugeritan Village, involving 10 participants. The results of the activity showed an increase in children's understanding of basic financial concepts, such as distinguishing between needs and wants and the importance of saving. Children are also more enthusiastic about implementing saving habits in their daily lives. This program is expected to be the first step in creating a young generation that is wise in managing finances.